Clinical effectiveness of a Bayesian algorithm for the diagnosis and management of heparin‐induced thrombocytopenia. (17th July 2017) - Raschke, R. A.; Gallo, T.; Curry, S. C.; Whiting, T.; Padilla‐Jones, A.; Warkentin, T. E.; Puri, A.
Abstract : Essentials We previously published a diagnostic algorithm for heparin‐induced thrombocytopenia (HIT). In this study, we validated the algorithm in an independent large healthcare system. The accuracy was 98%, sensitivity 82% and specificity 99%. The algorithm has potential to improve accuracy and efficiency in the diagnosis of HIT. Summary: Background: Heparin‐induced thrombocytopenia (HIT) is a life‐threatening drug reaction caused by antiplatelet factor 4/heparin (anti‐PF4/H) antibodies. Commercial tests to detect these antibodies have suboptimal operating characteristics. We previously developed a diagnostic algorithm for HIT that incorporated 'four Ts' (4Ts) scoring and a stratified interpretation of an anti‐PF4/H enzyme‐linked immunosorbent assay (ELISA) and yielded a discriminant accuracy of 0.97 (95% confidence interval [CI], 0.93–1.00). Objectives: The purpose of this study was to validate the algorithm in an independent patient population and quantitate effects that algorithm adherence could have on clinical care. Methods: A retrospective cohort comprised patients who had undergone anti‐PF4/H ELISA and serotonin release assay (SRA) testing in our healthcare system from 2010 to 2014. We determined the algorithm recommendation for each patient, compared recommendations with the clinical care received, and enumerated consequences of discrepancies. Operating characteristics were calculated for algorithm recommendations using SRA as the reference standard. Results: Analysis was performed on 181 patients, 10 of whom were ruled in for HIT. The algorithm accurately stratified 98% of patients (95% CI, 95–99%), ruling out HIT in 158, ruling in HIT in 10 and recommending an SRA in 13 patients. Algorithm adherence would have obviated 165 SRAs and prevented 30 courses of unnecessary antithrombotic therapy for HIT. Diagnostic sensitivity was 0.82 (95% CI, 0.48–0.98), specificity 0.99 (95% CI, 0.97–1.00), PPV 0.90 (95% CI, 0.56–0.99) and NPV 0.99 (95% CI, 0.96–1.00). Conclusions: An algorithm incorporating 4Ts scoring and a stratified interpretation of the anti‐PF4/H ELISA has good operating characteristics and the potential to improve management of suspected HIT patients.